Choice of basal insulin therapy is associated with weight and height development in type 1 diabetes: A multicenter analysis from the German/Austrian DPV registry in 10 338 children and adolescents - Vollbach, Heike; Auzanneau, Marie; Reinehr, Thomas; Wiegand, Susanna; Schwab, Karl-Otfried; Oeverink, Rudolf; Froehlich-Reiterer, Elke; Wölfle, Joachim; De Beaufort, Carine; Kapellen, Thomas; Gohlke, Bettina; Holl, Reinhard W. (Journal of Diabetes, 2021)
Background Available basal insulin regimes differ in pharmacokinetic profiles, which may be related to subsequent changes in anthropometry in patients with type 1 diabetes. This analysis elucidates the standardized height and body mass index development (height and BMI standard deviation score [height-SDS and BMI-SDS]) in pediatric type 1 diabetes patients depending on the choice of basal insulin. Methods Longitudinal data of 10 338 German/Austrian patients from the Diabetes Prospective Follow-up (DPV, Diabetes Patienten Verlaufsdokumentation) database were analyzed. Patients aged 5.0 to 16.9 years were treated exclusively with neutral protamine Hagedorn (NPH), insulin detemir (IDet), insulin glargine (IGla), or continuous subcutaneous insulin infusion (CSII) for at least 3 years. Population-based German reference data were used to calculate height-SDS and BMI-SDS. Multiple linear regression was conducted. Results BMI-SDS increased significantly in all regimes (NPH P = .0365; IDet P = .0003; IGla P < .0001; and CSII P < .0001). Direct comparison of the therapies revealed a favorable association only for NPH vs IGla. A rise in BMI-SDS was observed for all insulins in females, but only for IGla in males. BMI-SDS increment was not observed before 8 years of age. Initially and at the end of the observation period, mean height was above the 50th percentile of the reference population. Across the cohort, height-SDS declined during the observation period, except for CSII. Apart from the 5.0- to 7.9-year-old subgroup, long-acting insulin analogues were associated with a significant loss of height-SDS. Conclusions Choice of basal insulin regimen might influence height development. CSII appeared to have a favorable effect on growth trajectories. All therapies were associated with an increase of BMI-SDS, most evident in females.
CRIS-Team WoS Importer:2021-07-23